Review – H. pylori and non-malignant diseases - D. Bordin; M. Livzan; O. Gaus; S. Mozgovoi (Microbiota in Health and Disease)
The article considers the role of Helicobacter pylori (H. pylori) in the formation and progression of non-malignant diseases of the upper gastrointestinal tract and reviews the results of studies published in the period from April 2023 to May 2024. The association of H. pylori with gastroesophageal reflux disease remains controversial. However, eradication therapy has no significant effect on the formation of Barrett’s esophagus. There is an inverse relationship between H. pylori infection and the prevalence of eosinophilic esophagitis. H. pylori is still the main cause of chronic gastritis, which in some patients is accompanied by dyspepsia syndrome. Eradication of H. pylori can significantly improve morphologic features of atrophic gastritis and the severity of intestinal metaplasia at an early stage. The increased risk of gastric cancer in patients with autoimmune gastritis may be the result of previously unrecognized H. pylori infection. Against the background of a general trend towards a decrease in the prevalence of H. pylori-associated peptic ulcer disease, there is an increase in the proportion of drug-induced peptic ulcer disease, particularly among the older age group.